Neurological Symptoms and Their Associations With Inflammatory Biomarkers in the Chronic Phase Following Traumatic Brain Injuries - Li, Gangqin; Liu, Hao; He, Yong; Hu, Zeqing; Gu, Yan; Li, Yan; Ye, Yi; Hu, Junmei (Frontiers in Psychiatry, 2022)
Background The underlying biological mechanisms for neurological symptoms following a traumatic brain injury (TBI) remain poorly understood. This study investigated the associations between serum inflammatory biomarkers and neurological symptoms in the chronic phase following moderate to severe TBI. Methods The serum interleukin [IL]-1β, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12p70, and the tumor necrosis factor [TNF]-α in 72 TBI patients 6 months to 2 years post injury were measured. Neurological symptoms including depression, chronic headache, sleep disturbance, irritability, anxiety, and global neurological disability was assessed. The associations between the biomarkers and the neurological symptoms were assessed using correlation and regression analysis. Results It was found that the most common post-injury symptom was sleep disturbance (84.7%), followed by chronic headaches (59.7%), irritability (55.6%), and depression (54.2%). TNF-α was a protective factor for chronic headache (OR = 0.473, 95% CI = 0.235–0.952). IL-6 was positively associated with sleep disturbance (r = 0.274, p = 0.021), while IL-5 and IL-12p70 were negatively associated with the degree of global neurological disability (r = −0.325, p = 0.006; r = −0.319, p = 0.007). Conclusion This study provides preliminary evidence for the association between chronic inflammation with neurological symptoms following a TBI, which suggests that anti-inflammatory could be a potential target for post-TBI neurological rehabilitation. Further research with larger sample sizes and more related biomarkers are still needed, however, to elucidate the inflammatory mechanisms for this association.